Inclusiveness for all: the importance of individualization and differentiation for achieving educational progress in children in kindergarten - Rozalina Engels-Kritidis (Ignatianum University Press, 2017)
The publication outlines the importance of individualization and differentiation when selecting and developing educational content, as well as when planning the goals of pedagogical interactions in the kindergarten. The results of a study involving experimental and control groups of 3-4- and 6-7 year-old children are presented; they indicate greater improvement in the progress of children in the group where an individual and differentiated approach had been systematically applied to all pupils. Keywords: individualization; differentiation; individual educational progress; 3-4 year-old children; 6-7 year-old children.